Comparison between early and late mortalities due to severe sepsis in a pediatric intensive care unit: five-years-experience - Salah Rafik Zaher; Dina Adel Elgohary; Manal A. M. Antonios (Egyptian Pediatric Association Gazette, 2022)
Abstract Background The majority of children who die of sepsis suffer from refractory shock and/or multiple organ dysfunction syndrome, with many deaths occurring within the initial 48–72 h of treatment. Methods A retrospective observational study of deceased patients due to severe sepsis over 5 years, from the 1st of August 2015 to the end of July 2020, that were admitted in a pediatric intensive care unit. Results Over 5-year duration of the study, the trend of cases with severe sepsis increased from 26.4% in 2015 to 40.7% in 2020. Meanwhile, the trend of mortality among this category of patients dropped from 66.7% in 2015 to 33.9% in 2020. From the studied 163 deceased patients, results showed predominance of Klebsiella pneumoniae of the extended resistance pattern in bronchoalveolar lavage and blood cultures, and it came second to Candida in urine cultures. Pandrug-resistant organism was recorded in 8.59% (n = 14 patients). Patients with bacteremia, acidosis, high pediatric index of mortality (PIM-2), and pediatric logistic organ dysfunction (PELOD) scores were statistically related to early fatality fate. Conclusion High mortality was associated with the increasing spread of resistant organisms especially Klebsiella pneumoniae. Patients with bacteremia, acidosis, and high PIM-2 and PELOD scores probably will need immediate, vigorous, and intense care in order to save their lives.